Waste to Wealth: A Comprehensive Review of Agricultural Waste in Sustainable Building Materials - Pamu Yashwanth; Alugubelli Sanjana (E3S Web of Conferences)
As the global community grapples with the escalating challenges of waste management and environmental sustainability, the paradigm shift towards sustainable building practices emerges as a pivotal solution. This comprehensive review delves into the transformative potential of converting agricultural waste into valuable resources for the construction industry. The paper presents a comprehensive and detailed analysis of the utilization of such waste streams in various traditional building materials, encompassing concrete and cement products, aggregates, insulation materials, and bricks. By exploring the technical, economic, and environmental facets of these applications, the review aims to uncover the synergies and challenges associated with turning waste into wealth in construction. The discussion extends to reducing carbon footprints, waste diversion strategies, and adherence to regulatory standards. Through critical examination of current research, this review not only showcases successful implementations but also identifies research gaps and proposes future directions in the ongoing pursuit of greener and more resilient construction practices. In essence, “Waste to Wealth” advocates for a sustainable approach that not only addresses the mounting waste crisis but also propels the construction industry towards a more environmentally conscious and economically viable future.